With Stones in Our Hands : Writings on Muslims, Racism, and Empire - Rana, Junaid Akram, 1973-; Daulatzai, Sohail (Book collections on Project MUSE., 2018)
"After September 11, 2001, the Global War on Terror has made clear that Islam and Muslims are central to an imperial system of racism. Prior to 9/11, white supremacy has always had a violent relationship of dominance to Islam and Muslims. Racism against Muslims today borrows from centuries of white supremacy and is a powerful and effective tool to maintain the status quo. With Stones in Our Hands compiles writings by scholars and activists who are leading the struggle to understand and combat anti-Muslim racism. Through a bold call for a politics of the Muslim Left and the poetics of the Muslim International, this book offers a glimpse into the possibilities of social justice, decolonial struggle, and political solidarity. The essays in this anthology reflect a range of concerns that capture the contemporary moment such as anti-Muslim racism, the settler colonial occupation of Palestine, surveillance and policing, blackness and radical protest traditions, militarism and empire building, social movements, and political repression. The inaugural volume in the new series Muslim International, With Stones in Our Hands offers new ideas to achieve decolonization and global solidarity"--